Macathiohydantoin L, a Novel Thiohydantoin Bearing a Thioxohexahydroimidazo [1,5-a] Pyridine Moiety from Maca (Lepidium meyenii Walp.) - Zhang, Ranran; Liu, Junhong; Yan, Hui; Peng, Xingrong; Zhang, Ling; Qiu, Minghua (Molecules (Basel, Switzerland), 2021)
Five new thiohydantoin derivatives (1–5) were isolated from the rhizomes of Lepidium meyenii Walp. NMR (1H and 13C NMR, 1H−1H COSY, HSQC, and HMBC), HRESIMS, and ECD were employed for the structure elucidation of new compounds. Significantly, the structure of compound 1 was the first example of thiohydantoins with thioxohexahydroimidazo [1,5-a] pyridine moiety. Additionally, compounds 2 and 3 possess rare disulfide bonds. Except for compound 4, all isolates were assessed for neuroprotective activities in corticosterone (CORT)-stimulated PC12 cell damage. Among them, compound (−)-3 exhibited moderate neuroprotective activity (cell viability: 68.63%, 20 μM) compared to the positive control desipramine (DIM) (cell viability: 88.49%, 10 μM).